2015
DOI: 10.1371/journal.pone.0118639
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors for Men’s Lifetime Perpetration of Physical Violence against Intimate Partners: Results from the International Men and Gender Equality Survey (IMAGES) in Eight Countries

Abstract: This paper examines men’s lifetime physical intimate partner violence (IPV) perpetration across eight low- and middle-income countries to better understand key risk factors that interventions can target in order to promote gender equality and reduce IPV. We use data from men (n = 7806) that were collected as part of the International Men and Gender Equality Survey (IMAGES) in Bosnia and Herzegovina, Brazil, Chile, Croatia, Democratic Republic of Congo (DRC), India, Mexico, and Rwanda. Results show that there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
189
4
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(233 citation statements)
references
References 54 publications
18
189
4
22
Order By: Relevance
“…This study found, in agreement with previous studies (Fleming et al 2015;Gass et al, 2011, Ishida et al, 2010Peitzmeier et al 2016), an association common mental disorders and/or community violence victimization with IPV victimization and/or perpetration among women and/or men. However, contrary to these study findings common mental disorders have commonly been seen as a sequela of IPV, and not as a risk factor (Gass et al, 2011).…”
Section: Association Between Independent Variables and Ipv Victimizatsupporting
confidence: 93%
See 3 more Smart Citations
“…This study found, in agreement with previous studies (Fleming et al 2015;Gass et al, 2011, Ishida et al, 2010Peitzmeier et al 2016), an association common mental disorders and/or community violence victimization with IPV victimization and/or perpetration among women and/or men. However, contrary to these study findings common mental disorders have commonly been seen as a sequela of IPV, and not as a risk factor (Gass et al, 2011).…”
Section: Association Between Independent Variables and Ipv Victimizatsupporting
confidence: 93%
“…Previous studies in South Africa and elsewhere (Fleming et al, 2015;Gass et al, 2011;Peitzmeier et al, 2016) seem to have found higher rates of IPV perpetration, although lifetime rates were reported that are difficult to comapre with 12-month rates. The study also found high rates of co-occurrence of IPV victimization and perpetration, especially among IPV perpetrators, among both women and men.…”
Section: Association Between Independent Variables and Ipv Victimizatmentioning
confidence: 79%
See 2 more Smart Citations
“…Ello en el marco de un orden patriarcal que históricamente ha discriminado y generado desigualdades hacia las mujeres. (Barker y Aguayo, 2012;Fleming et al, 2015;Ramírez, 2008;Jewkes et al, 2011).…”
Section: Violencia Contra Las Mujeres Niñas Y Niños (Vcmn) En Américunclassified